The Effectiveness of Collaborative Learning in Improving English Writing Skills in Higher Education - Khusnul Khatimah, Elsa; Ilham, Ilham; Humairah, Humairah (Journal of English Culture, Language, Literature and Education, 2025)
The study investigates the effectiveness of collaborative learning in improving English writing skills among higher education students. Despite widespread advocacy for collaborative learning, there remains a significant gap in understanding its specific impact on various aspects of writing, such as coherence, grammar, and vocabulary use. The research employs a Systematic Literature Review (SLR) approach to synthesize findings from recent studies (2018-2024) on collaborative learning in writing instruction. Key findings reveal that collaborative learning, particularly through peer feedback and real-time digital tools like Google Docs, enhances students’ writing skills in coherence, grammar, and vocabulary. The study also identifies the role of technology in facilitating collaborative processes and highlights challenges such as time management and student engagement. Pedagogical implications include the need for structured group activities, the integration of digital tools, and instructor facilitation to optimize the benefits of collaborative learning. This research contributes to the field by providing a comprehensive analysis of collaborative learning’s impact on writing skills, offering insights for educators to enhance writing instruction in higher education.